Perancangan Ulang UI/UX Website SMPN 3 Genteng Menggunakan Metode Design Thinking - Putri, Safira Tsani Amelya; Umam, Khoirul; Panduardi, Farizqi; Prasetyo, Junaedi Adi; Hidayat, Alfin (Jurnal Informatika dan Komputer, 2025)
SMPN 3 Genteng faces challenges in providing information that is easy to understand and visually appealing to users. The current website has a disorganized layout, making it difficult for users to find information about school services. An evaluation using the System Usability Scale (SUS) revealed a usability score of 41.58, rated as "Awful." Based on this evaluation, a redesign of the User Interface and User Experience (UI/UX) using the Design Thinking method was necessary. The redesign process was carried out through five stages: empathize, define, ideate, prototype, and test. The solutions developed included improving the layout, enhancing the functionality of the menu, and creating a new prototype. This prototype was then evaluated using the SUS method, resulting in a score of 82 with a "Good" rating, indicating a significant improvement in the website's interface. The goal of this research was to enhance the usability and user experience (UI/UX) so that information about school services can be accessed more efficiently and pleasantly. The results show that the redesign successfully met user needs and improved their interaction with the school's website.